READERLY INNOCENCE, MORAL SHOCK, AND INSTITUTIONAL AUTHORITY: A READER-RESPONSE ANALYSIS OF PENELOPE ROWE’S THE INNOCENTS - Yulhenli Thabran (Universitas Islam Sumatera Utara (UISU), 2026)
This study is among the first to examine moral shock and narrative indeterminacy in Penelope Rowe’s The Innocents through reader-response criticism. While scholarship on ethically disturbing fiction often emphasizes thematic or ideological critique, less attention has been paid to how readerly affect evolves during the act of reading. Addressing this gap, the article employs a qualitative reader-response–oriented close textual analysis to investigate how sympathy, moral destabilization, and narrative indeterminacy structure interpretation. Rather than presenting empirical reader data, the analysis focuses on implied reader positions embedded in the text. The findings identify three interrelated mechanisms. First, innocence is constructed affectively through narrative alignment with the child protagonist. Second, moral shock destabilizes trust in institutional authority by exposing interpretive rigidity. Third, the open ending withholds psychological closure and transfers ethical responsibility to the reader. These responses are not incidental reactions but structured aesthetic strategies that generate the story’s ethical force. By demonstrating how affect, indeterminacy, and reader positioning operate together, this article advances reader-response criticism and literary ethics, showing how discomfort and uncertainty function as mechanisms of ethical meaning-making in morally unsettling short fiction.